Effects of drafting during short-track speed skating - Rundell, K. W. (Medicine & Science in Sports & Exercise, 1996)
Short-track speed skating involves pack-style racing where five to seven skaters may be on the ice at once. Since average speed for a 3000-m event may exceed 35 km.h-1, drafting may be beneficial. However, the short (111 m) oval track could limit effective drafting space, and high forces required in cornering may compromise potential benefits. We evaluated heart rate (HR)-lactate (LA) responses and post-drafting 3-lap sprint performance using 18 National Team and developmental skaters. Two 4-min trials, one drafting and one leading at 8.8 m.s-1, were performed. In addition, six skaters performed three 3-lap sprints, rested, immediately after a 4-min drafting trial at 9.2 m.s-1, and immediately after an unaided 4-min trial at 9.2 m.s-1. Results demonstrated lower HR and LA responses during drafting (174.0 +/- 9.0 and 5.56 +/- 2.18 vs 180.4 +/- 8.7 and 7.75, P < 0.05) at 8.8 m.s-1. After 4-min trials at 9.2 m.s-1, HR deltas were 6 bpm, lactate values were 9.00 +/- 1.84 and 5.22 +/- 1.18 for unaided and drafting, respectively. Sprint performance was better following drafting (33.46 +/- 1.19 vs 34.03 s, P < 0.05). HR and LA deltas during the 8.8 m.s-1 trials ranged from 0.8 to 12.4 and -0.18 to 5.37, respectively, indicating that some skaters were more effective drafters than others. These results suggest that drafting could be an important strategy in short-track speed skating, and drafting technique should be emphasized in training.